Embracing Change: A Mindful Medical Center Meets COVID-19 - Maryanna D Klatt PhD; Rani Bawa; Olivia Gabram BS; Amanda Blake MPH; Beth Steinberg MS, RN, NEA-BC; Alexis Westrick; Scott Holliday MD, FACP, FAAP (SAGE Publishing, 2020)
Background Healthcare professional (HCP) burnout transcends clinician job title and role, thus creating a need for interprofessional strategies to address burnout. The organizational framework of offering employer-sponsored mindfulness programming to HCPs sets the stage for an orchestrated, mindful response to COVID-19. Objective This single arm pre-post interventional research tested changes in measures of burnout, resilience, perceived stress and work engagement for interprofessional HCP faculty and students participating in Mindfulness in Motion (MIM) , a novel eight-week multimodal evidenced-based onsite intervention. Methods A Graduate Medical Education (GME) pilot of MIM was expanded to target inter-professional resiliency within an academic health center. MIM is the core offering of the Gabbe Health and Wellness program for students, staff, faculty, and residents and is embedded across the entire medical center. Results The faculty/student role demographic categories (n = 267) included resident physicians, resident chaplains, attending physicians, medical center faculty, and hospital administrative/managerial clinical staff. These cohorts demonstrated significant 27% reduction in participants meeting burnout criteria. Total burnout was determined by scores on subscales of emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA) of the Maslach Burnout Inventory (MBI). There was a highly significant pre/post decrease in the in the emotional exhaustion (p < 0.00001) and depersonalization scores (p < 0.001), with highly significant increase in the personal accomplishment (p < 0.00001) scores. Resilience, as measured by the Connor Davidson Resiliency Scale (CDRS), significantly increased (p < 0.00001), alongside a significant increase (p < 0.00001) in the total Utrecht Work Engagement Score (UWES) and a significant decrease in scores on the Perceived Stress Scale (PSS) (p < 0.00001). Conclusion MIM significantly reduced burnout and perceived stress, for interprofessional (HCP) faculty and staff, while increasing resilience and work engagement in a large healthcare system. These results paved the way for an organizational response that utilized mindfulness to empower HCPs to navigate through the novel challenges presented by COVID-19.